The Progress in Diagnosis and Treatment of Exosomes and MicroRNAs on Epileptic Comorbidity Depression - Wei, Nian; Zhang, Haiqing; Wang, Jing; Wang, Shen; Lv, Wenbo; Luo, Limei; Xu, Zucai (Frontiers in Psychiatry, 2020)
The occurrence of epilepsy can increase the incidence of depression, and the risk of epilepsy in the patients with depression is also high, both of which have an adverse effect on the life and the psychology of the patient, which is not conducive to the prognosis of the patients with epilepsy. With lucubrating the function of exosomes and microRNAs, some scholars found that the exosomes and its microRNAs have development prospect in the diagnosis and treatment of the disease. MicroRNAs are involved in the regulation of seizures and depression, as biomarkers, that can significantly improve the management of epileptic patients and play a preventive role in the occurrence of epilepsy and epilepsy depressive disorder. Moreover, due to its regulation to genes, appropriate application of microRNAs may have therapeutic effect on epilepsy and depression with the characteristics of long distance transmission and stability of exosomes, to a certain extent. This provides a great convenience for the diagnosis and treatment of epileptic comorbidity depression.